Every Man Has His Breaking Point : the Attitudes of American Infantrymen Towards Combat Fatigue in World War II - Johnson, Paul M. (My University, 2007)
My intention with this paper is to reveal both how complicated the combat fatigue problem was and how tempting simplistic views of it were. I seek to show how "average" combat soldiers in World War II perceived it at the individual level and how collectively they paint a complex picture. They developed a framework of understanding psychiatric casualties with certain assumptions in place, developed criteria from which to assess individual cases. These assumptions and criteria emerged from the reality of their experience, especially the situational factors over which they had no control but were crucially influential in their outlook. These criteria included the effort expended to maintain control, the pride which kept them from verbally invoking their reaction and symptoms as an excuse to get out of fighting, and the appearance of loyalty to the primary group, at least a display of reluctance to "abandon" it. There were two kinds of stigma that existed, both of which were limited to the context of wartime realities. Combat veterans had a complex understanding of combat fatigue, even though it was often expressed crudely. Their own "strength" was subject to fluctuations and in some cases a steady decline. That truth blurs the line between the "weak" and the "strong." One of the underlying factors influencing the attitudes of combat men toward combat fatigue was an intense and widespread resentment toward the Army. The attitudes of combat soldiers were far from simple, but essentially they agreed that every man had his breaking point. In part, due to situational factors over which they had no control, and in part due to small group dynamics, they established criteria with which they could "judge" individual cases of combat fatigue by. They withheld their full approval when certain criteria were not met, even if they were inclined to grant the universal vulnerability.
Keywords: War neuroses--History--20th century.; Combat--Psychological aspects.; Soldiers--United States--Attitudes--History--20th century.; United States. Army--Armed Forces--Attitudes.; World War, 1939-1945--Psychological aspects.